Using Low-Level Architectural Features for Configuration InfoSec in a General-Purpose Self-Configurable System - Macias, Nicholas J.; Athanas, Peter M. (International Journal of Advanced Science and Technology, 2010)
Unique characteristics of biological systems are described, and similarities are made to certain computing architectures. The security challenges posed by these characteristics are discussed. A method of securely isolating portions of a design using introspective capabilities of a fine-grain self-configurable device is presented. Experimental results are discussed, and plans for future work are given.